2021
DOI: 10.1039/d0cp03777j
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational energy relaxation of interfacial OH on a water-covered α-Al2O3(0001) surface: a non-equilibrium ab initio molecular dynamics study

Abstract: Vibrational dynamics and relaxation of excited non-hydrogen bonded OH-aluminols from non-equilibrium AIMD, towards in silico time-resolved VSF experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…Reprinted with permission from Ref. [226]; permission conveyed through Copyright Clearance Center, Inc…”
Section: Types Of Spectroscopymentioning
confidence: 99%
“…Reprinted with permission from Ref. [226]; permission conveyed through Copyright Clearance Center, Inc…”
Section: Types Of Spectroscopymentioning
confidence: 99%
“…48 It has been applied in a limited way to compute spectra at solid interfaces, for example (liquid) water on CaF 2 , 49 hydroxylated and (deuterated) water-covered alumina surface. 50,51 It has not established itself in mechanistic studies of molecule-surface systems, in particular in the field of heterogeneous catalysis. A major difficulty is the absence of potential energy surfaces for most (an overwhelming majority) molecule-surface systems studied in laboratories.…”
Section: Perspective Pccpmentioning
confidence: 99%
“…Recently, Saalfrank and co-workers implemented nonequilibrium AIMD (NE-NVE/AIMD) simulations to excite upright non-hydrogen-bonded aluminol groups at the water covered α-Al 2 O 3 (0001)/H 2 O interface (Figure 19). 101 The authors chose to focus on the excitation of weakly hydrogen-bonded aluminol groups, which were orientationally flexible and at room temperature were able to switch between upright and parallel with the surface. It was found that, following excitation of the upright aluminol groups, energy transfer directly to the alumina surface phonons was not significant in the relaxation process.…”
Section: Vibrational Dynamics Nearmentioning
confidence: 99%
“…Although the system was constrained in size and scope by the cost of the simulations, Saalfrank and coworkers mentioned that the NE-NVE/AIMD approach is not limited in the ways that a parametrized force field is, allowing for the method to be implemented in other avenues. 101…”
Section: Vibrational Dynamics Nearmentioning
confidence: 99%
See 1 more Smart Citation